Metody wizualizacji danych sieciowych - Kowalska-Musiał, Magdalena (Methods of Network Data Visualization, 2009)
In social network analysis, graphic methods of visualization are of particular significance - both of relations among interacting objects, and of formal attributes of networks and sub-networks formed on the basis of those interactions. The paper presents methods of network visualization in the retrospective picture, as well as problems of contemporary packages intended for SNA analysis.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 86, s. 223-231